Efektifitas Edukasi Kesehatan terhadap Perilaku Pencegahan Malaria: Tinjauan Pustaka - Landudjama, Leni; Noviana, Ineke; Kitu, Irene Febriany Mamo (JURNAL KESEHATAN PRIMER, 2021)
Background: Malaria is an infectious disease caused by the Plasmodium parasite and transmitted to humans through the bite of the Anopheles mosquito. Efforts to prevent malaria are carried out through the implementation of health education about malaria to the community. Objective: to identify the effectiveness of health education on malaria prevention behavior. Method: This type of research is a literature review, literature search using the Google Scholar database with the keyword 'Effectiveness of Health Education on Malaria Prevention Behavior'. Inclusion criteria are journals published in the period 2019-2020, the type of original journal articles with quantitative, qualitative research methods, reviews with journals that can be fully accessed via full text pdf, the articles taken are national and international journal articles. Results: the effectiveness of health education has been proven effective in improving malaria prevention behavior by involving increased knowledge, changing attitudes, and encouraging the implementation of malaria prevention behavior by individuals, families and communities. An effective health education program uses an approach that is in accordance with the characteristics of the community, involves various parties, and is implemented periodically.